Design Issues and Inference in Experimental L2 Research. Issue 1 (June 2015) - Hudson, Thom; Llosa, Lorena; Norris, John M.; Ross, Steven J.; Schoonen, Rob
<x xml:space="preserve">Abstract</x> Explicit attention to research design issues is essential in experimental second language (L2) research. Too often, however, such careful attention is not paid. This article examines some of the issues surrounding experimental L2 research and its relationships to causal inferences. It discusses the place of research questions and hypotheses, threats to internal and external validity, specific experimental designs, sample size, and the language used in discussing causal relationships. It is hoped that this discussion will bring design issues to the forefront in experimental L2 research.